2017
DOI: 10.18632/oncotarget.20155
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles of yes-associated protein (YAP) in colorectal cancer

Abstract: Yes-associated protein (YAP) is a downstream effector molecule of a newly emerging tumour suppressor pathway called the Hippo pathway. YAP is a transcriptional co-activator and mis-expressed in various cancers, including colorectal cancer (CRC). Accumulating studies show that the high expression of nuclear YAP is linked with tumour progression and decreased survival. Nuclear YAP can interact with other transcription factors to promote cancer cell proliferation, apoptosis, metastasis and maintenance of stemness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 193 publications
(223 reference statements)
2
42
0
Order By: Relevance
“…In 2015, 777,987 new cases and 352,589 deaths occurred due to CRC [30]. With the development of basic and clinical investigations, the mechanisms of CRC and therapeutic strategies involved have become better understood [31]. Nevertheless, due to postsurgical recurrence and metastasis of primary tumours, CRC mortality and morbidity rates remain high.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, 777,987 new cases and 352,589 deaths occurred due to CRC [30]. With the development of basic and clinical investigations, the mechanisms of CRC and therapeutic strategies involved have become better understood [31]. Nevertheless, due to postsurgical recurrence and metastasis of primary tumours, CRC mortality and morbidity rates remain high.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review has highlighted the bilateral roles of Yap, as both a tumor suppressor and an oncogene in CRC. Nuclear Yap overexpression has been observed in various cancers, including CRC, and correlates inversely with OS and DFS .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that YAP is an oncogenic gene, which is highly expressed in various tumors and can regulate tumor progression. 23 – 25 Nuclear YAP can promote cancer cell proliferation, apoptosis, metastasis, and maintenance of stemness by interacting with other transcription factors and affecting tumor progression. Therefore, YAP has the prospect of being a new tumor biomarker or therapeutic target for CRC.…”
Section: Introductionmentioning
confidence: 99%